ANALISIS FAKTOR INTERNAL DAN EKSTERNAL DALAM PENGEMBANGAN STRATEGI BISNIS UNTUK MENINGKATKAN PERMINTAAN EKSPOR PRODUK PERIKANAN DI STARTUP DIGITAL X - Aulia, Renita; Nurhayati, Atikah; Andriani, Yuli; Maulina, Ine (Universitas Pattimura, 2025)
The purpose of this research is to analyze the business strategy at Startup Digital X through the identification of the company's internal and external factors, which are used as the basis for making important decisions in the fishing business. The research was conducted at Startup Digital X on May 13, 2024 - June 14, 2024 using the case study method. Primary and secondary data were collected using purposive sampling technique. Data analysis was carried out descriptively quantitatively using SWOT analysis. The results of the internal analysis show that the company's strengths, such as product quality and operational efficiency, are more dominant than its weaknesses. While from external factors, opportunities in market expansion and product innovation are greater than threats such as fluctuations in raw material prices. The company is in a favorable position (Quadrant I), allowing the implementation of an aggressive growth strategy. The SWOT matrix results in nine alternative strategies grouped into four types: backward integration, market penetration, market development, and product development.